Analisis Kondisi Jalan Yonif 407-Tugu 0 KM Slawi II - Icha Yaunisha, Cheryl Fara; Milasari, Adhistina Dewi; Saputro, Johan Fatkhurrozi; Nugroho, Rizky Reynaldi; Hadi, Suprapto (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Abstract               Inadequate road infrastructure will affect the safety of road users. So it is necessary to have road conditions that meet regulatory standards. This supervision is carried out to manage road assets for safety. Surveillance is carried out along Jalan Yonif 407-Tugu 0 KM Slawi II. This research aims to present the results of quantitative and qualitative surveys based on measurements of safety deficiencies in the field so that they can become a reference for making improvements. Data and information collection as well as inventory of existing data is then carried out on the data and by comparing using standards according to existing regulations and standards. The survey results obtained data on road equipment, IRI values, volume, speed and degree of saturation. and the condition of existing road equipment, as well as the 85th percentile speed. From the analysis results obtained, road conditions still have many deficiencies. The road equipment on this road is still incomplete and many road equipment are damaged. The condition of the road surface is still in the good category, it's just that there are several road sections that have lots of patches, cracks and holes. Level of services C which means stable flow but vehicle movement is controlled by a higher traffic volume with a speed of at least 60 km/h, moderate traffic density and increased internal traffic resistance, drivers have limitations in choosing speed, changing lanes or overtaking. Therefore, improvements are needed to create road safety. Keywords—volume, safety, road equipment